2021
DOI: 10.1038/s41467-021-27326-0
|View full text |Cite|
|
Sign up to set email alerts
|

Biological heterogeneity in idiopathic pulmonary arterial hypertension identified through unsupervised transcriptomic profiling of whole blood

Abstract: Idiopathic pulmonary arterial hypertension (IPAH) is a rare but fatal disease diagnosed by right heart catheterisation and the exclusion of other forms of pulmonary arterial hypertension, producing a heterogeneous population with varied treatment response. Here we show unsupervised machine learning identification of three major patient subgroups that account for 92% of the cohort, each with unique whole blood transcriptomic and clinical feature signatures. These subgroups are associated with poor, moderate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 65 publications
(52 reference statements)
2
30
0
Order By: Relevance
“…Our observations are in alignment with those of Kariotis and colleagues, who identified three whole-blood transcriptomic patient subgroups of IPAH patients that accounted for more than 90% of the cohorts 22 . These subgroups were associated with poor, moderate, and good prognoses.. Our study also extends to CTEPH patients, suggesting that the metabolic phenotypes are not restricted to PAH.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations are in alignment with those of Kariotis and colleagues, who identified three whole-blood transcriptomic patient subgroups of IPAH patients that accounted for more than 90% of the cohorts 22 . These subgroups were associated with poor, moderate, and good prognoses.. Our study also extends to CTEPH patients, suggesting that the metabolic phenotypes are not restricted to PAH.…”
Section: Discussionsupporting
confidence: 91%
“…Important work remains in characterizing biomarkers of inflammasome activation in patients with PAH arising from diverse causes. Several such efforts are underway currently, and have reported novel potential groupings of PAH patients based on sequencing efforts ( 59 , 60 ). Once a systematic assessment has been made, clinical trials can begin in targeted populations most likely to derive benefit from these translational therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Some PAH gene mutations, such as the gene encoding bone morphogenetic protein type 2 receptor (BMPR2) protein, have been identified by whole-genome sequencing [ 17 ]. A recent study showed that unsupervised machine learning analysis of the whole blood transcriptome of IPAH patients could divide 92% of IPAH patients into three subgroups, each with unique whole blood transcriptomic and clinical features associated with prognosis [ 18 ]. These studies may indicate genetic differences in PAH.…”
Section: Discussionmentioning
confidence: 99%